2005
DOI: 10.1182/blood-2005-04-1407
|View full text |Cite|
|
Sign up to set email alerts
|

Only a specific subset of human peripheral-blood monocytes has endothelial-like functional capacity

Abstract: The monocyte population in blood is considered a possible source of endothelial precursors. Because endothelial-specific receptor tyrosine kinases act as regulators of endothelial cell function, we investigated whether expression of the vascular endothelial growth factor receptor-2 (VEGFR-2) on monocytes is important for their endothelial-like functional capacity. Peripheral-blood monocytes expressing vascular endothelial growth factor receptor-2 (VEGFR-2), or CD14 ؉ /VEGFR-2 ؉ , were isolated, and their pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 33 publications
5
75
0
Order By: Relevance
“…This finding is consistent with results from several laboratories that have reported circulating cells with myeloid features contributing to human angiogenesis (8)(9)(10)(11). Importantly, we have also shown that donor-derived endothelial cells differentiate from myeloid progenitors and are not products of cell fusion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with results from several laboratories that have reported circulating cells with myeloid features contributing to human angiogenesis (8)(9)(10)(11). Importantly, we have also shown that donor-derived endothelial cells differentiate from myeloid progenitors and are not products of cell fusion.…”
Section: Discussionsupporting
confidence: 82%
“…Human circulating and bone marrow-derived endothelial progenitor activity has previously been reported in transplant recipients (6,7). However, functional studies of human endothelial progenitors (8)(9)(10)(11) have mainly relied on in vitro assays. Although expression of the myelomonocytic marker CD14 appears to be a common feature of these circulating progenitors, it has been challenging to determine both the phenotype and origin of these cells.…”
mentioning
confidence: 99%
“…Most importantly, previous studies showed that CD14 + KDR + cells exhibit the potential to differentiate into cells with endothelial characteristics both in vitro and in vivo (Nowak et al 2004;Elsheikh et al 2005). Our study showed CD14 + KDR + cells constituting approximately 2.02%±1.41% of the total population of monocytes in the blood, which is very closely to the observation of Elsheikh et al (2005) (2%±0.5%). The number of CD14 + KDR + cells in the blood was not significantly different in controls compared with patients with stable CAD or ACS.…”
Section: Determinants Of Circulating Cd14 + -Epcs Levelssupporting
confidence: 86%
“…5,13 Also accumulating evidence supports the hypothesis that a population of circulating CD14 þ monocytes can be a source of EPCs. 14,15 Moreover, Krankel et al 16 showed that type B2 receptor for bradykinin is expressed on EPCs. The presence of type B2 receptor is consistent with the chemoattractant effects of bradykinin, which in turn is guided by the migration of proangiogenic progenitor cells.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%